2015
DOI: 10.1177/1528083715580543
|View full text |Cite
|
Sign up to set email alerts
|

A microbiological evaluation of SiO2-coated textiles in hospital interiors: The effect of passive coatings on the cleaning potential of interior textiles

Abstract: The use of passive coatings could be a new solution to improve the cleaning potential of interior textiles in hospitals. In these years, the scepticism toward the use of antibacterial textiles in the health care sector is emerging, and in the Nordic countries, the implementation success is confined. From this perspective, the purpose of this paper is therefore to address focus on alternative passive coatings that without actively killing the bacteria provide a hydrophobic and easy-to-clean textile surface. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…9 Nano SiO2 treated textiles have provided better microbiological controls in hospital interiors. 10 A significant result was observed in the zinc oxide nanoparticle treated cotton fabrics against S.Aureus. 11 In the ZnO/TiO2 composite treated nylon/cotton blended fabric, the highest antibacterial property against E.coli and S.Aureuswas obtained at a concentration of 60 ppm.…”
Section: Introductionmentioning
confidence: 95%
“…9 Nano SiO2 treated textiles have provided better microbiological controls in hospital interiors. 10 A significant result was observed in the zinc oxide nanoparticle treated cotton fabrics against S.Aureus. 11 In the ZnO/TiO2 composite treated nylon/cotton blended fabric, the highest antibacterial property against E.coli and S.Aureuswas obtained at a concentration of 60 ppm.…”
Section: Introductionmentioning
confidence: 95%
“…The functionalization of textile products for use as personal protective equipment (PPE), filters, sensors, clothing, interior materials, and so on is being actively pursued in various industries, such as hygiene, interior design, and medical care, using fiber as the substrate [1][2][3]. In particular, owing to the recent COVID-19 pandemic, the development of PPE products is needed to protect the human body from external bacteria or viruses and harmful substances.…”
Section: Introductionmentioning
confidence: 99%
“…12 Nanoscale silicon dioxide has been used in hospital environments. 13 Silicon dioxide coating results in a surface with a massively reduced amount of microorganisms and is easy to clean. In addition, silicon dioxide has been shown to be effective in reducing the adhesion of C. albicans to acrylic resin surfaces 14,15,16 and a recent in vivo study has demonstrated a high level of tissue biocompatibility of acrylic resin coated with silicon dioxide with low deleterious risk to patients.…”
Section: Introductionmentioning
confidence: 99%